2021
DOI: 10.1002/anie.202111920
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction‐Based Electron Donators to Stabilize and Activate Ultrafine Pt Nanoparticles for Efficient Hydrogen Atom Dissociation and Gas Evolution

Abstract: Platinum (Pt) is the most effective bench-marked catalyst for producing renewable and clean hydrogen energy by electrochemical water splitting. There is demand for high HER catalytic activity to achieve efficient utilization and minimize the loading of Pt in catalysts. In this work, we significantly boost the HER mass activity of Pt nanoparticles in Pt x /Co to 8.3 times higher than that of commercial Pt/C by using Co/NC heterojunctions as a heterogeneous version of electron donors. The highly coupled interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…The utilization of hydrogen energy is considered to be one of the important ways to reduce CO 2 emissions from traditional fossil fuel combustion. The water splitting is an efficient and clean approach to develop hydrogen energy, especially using the electricity generated by renewable energy. The recognized catalyst used to produce hydrogen efficiently through water splitting is the expensive and scarce Pt, which shows the best hydrogen evolution reaction (HER) performance for the most appropriate metal–H bond strength according to the typical Sabatier principle . However, this principle alone cannot explain the phenomenon that the HER activity of Pt under alkaline media is 2–3 orders of magnitude worse than that under acidic media. ,, It is suggested that the energy barrier of water dissociation under alkaline media is the key factor restricting the catalyst’s HER activity. , The recent studies show that ruthenium (Ru), which costs only about one-third of the price of Pt, shows superb HER activity under acidic or alkaline media. , Thanks to the water dissociation and *OH chemisorption capacity, many Ru-based catalysts show better HER performance than Pt under alkaline media. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The utilization of hydrogen energy is considered to be one of the important ways to reduce CO 2 emissions from traditional fossil fuel combustion. The water splitting is an efficient and clean approach to develop hydrogen energy, especially using the electricity generated by renewable energy. The recognized catalyst used to produce hydrogen efficiently through water splitting is the expensive and scarce Pt, which shows the best hydrogen evolution reaction (HER) performance for the most appropriate metal–H bond strength according to the typical Sabatier principle . However, this principle alone cannot explain the phenomenon that the HER activity of Pt under alkaline media is 2–3 orders of magnitude worse than that under acidic media. ,, It is suggested that the energy barrier of water dissociation under alkaline media is the key factor restricting the catalyst’s HER activity. , The recent studies show that ruthenium (Ru), which costs only about one-third of the price of Pt, shows superb HER activity under acidic or alkaline media. , Thanks to the water dissociation and *OH chemisorption capacity, many Ru-based catalysts show better HER performance than Pt under alkaline media. ,, …”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the incorporation of adjacent CoNi nanoparticles as solid ligands regulates the charge distribution of Co central atoms in Co–N x –C, which downshifts the d-band central energy level so as to weaken the adsorption of *OH intermediates. In addition the strong coupling effect in atom–particles composites is conducive to anchor the alloy particles and effectively inhibit their aggregation, detachment, and Ostwald ripening, 74 thus enhancing the electrocatalytic stability. Finally, N-doped carbon matrix with a large specific surface area and rich porosity are favorable for accelerated the penetration and diffusion of electrolytes and oxygen during the ORR process.…”
Section: Resultsmentioning
confidence: 99%
“…As a typical example of electron‐rich metal based electrocatalysts, Sun et al [16] . synthesized electron‐rich and ultra‐fine Pt nanoparticles by using Co/NC heterojunction as effective “solid ligands”.…”
Section: Figurementioning
confidence: 99%
“…As a typical example of electron-rich metal based electrocatalysts, Sun et al [16] synthesized electron-rich and ultra-fine Pt nanoparticles by using Co/NC heterojunction as effective "solid ligands". The as-obtained electron-rich Pt nanocatalysts could act as highly effective hydrogen evolution reaction (HER) catalyst with very low HER overpotential.…”
mentioning
confidence: 99%